Anthropometric analysis between Naso-aural Inclination and Their Correlation in Bangladeshi Buddhist Rakhain Ethnic Males - Iqbal, Mohammed; Nahar, Nazmun; Naheen, Towhida; Mohi Uddin, SK Amin; Begum, Farzana; Rahman, Mizanur; Rahman, Kazi Md Shahidur; Biawas, Utpal Kumar (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Naso-aural Inclination most prominent structure of the face, influencing facial appearance and profile. Objective: The aim of the study was to describe anthropometric analysis between naso-aural inclination and their correlation in Bangladeshi Buddhist Rakhain Ethnic males. Methodology: This cross-sectional observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2011 to December 2011 for a period of one (01) year. Adult healthy Bangladeshi Buddhist Rakhain males with the age group of 18 to 30 years were included as study population. Standard of normative facial anthropometric values related to nose inclination and ear inclination. Result: A total number of 100 adult healthy Bangladeshi Buddhist Rakhain males were recruited for this study. The mean nose inclination was 32±4.38 degree and ear inclination left was 15.64±3.85 degree. Conclusion: In conclusion the standard of normative facial anthropometric values related to nose inclination is significantly greater than ear inclination among the Bangladeshi Buddhist Rakhain males. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):62-64